Juridical Analysis of the Imposition of Punishment on Perpetrators of Corruption Crimes Committed Jointly : (Study of Decision Number: 88/Pid.Sus-TPK/2021/PN Mdn Jo Decision Number: 18/Pid.Sus-TPK/2022/PT Mdn) - Asmawiah Nainggolan; Ismaidar Ismaidar; Chairuni Nasution (International Journal of Law and Society, 2024)
Criminal accountability by perpetrators of criminal acts of corruption committed individually or collectively is very important in eradicating criminal acts of corruption and providing a deterrent effect to perpetrators of criminal acts of corruption. Corruption currently occurring in Indonesia is in a very serious position and is deeply rooted in every aspect of life. The development of corrupt practices from year to year is increasing, both in terms of the quantity or amount of state financial losses and in terms of quality, which is increasingly systematic, sophisticated and its scope has expanded in all aspects of society.The method used in this research is descriptive analysis. Research data sources are generally distinguished between data obtained from library materials (secondary data). Normative legal research methods only recognize secondary data. The secondary data consists of primary legal materials, secondary legal materials and tertiary legal materials. In this research the author used qualitative analysis to analyze the data. Where qualitative analysis is a way of analyzing data sourced from legal materials based on concepts, theories, statutory regulations, doctrine, legal principles and expert opinions as well as the author's own views.This research aims to find and examine more deeply the legal instruments in the context of accountability for perpetrators of criminal acts of corruption committed jointly. The results of this research are influenced by certain factors, and as a result of acts of corruption, responsibility can be imposed on perpetrators of criminal acts of corruption, not only those who commit corruption individually, but also those who do it together.